2016
DOI: 10.1371/journal.pbio.1002461
|View full text |Cite
|
Sign up to set email alerts
|

Release of GTP Exchange Factor Mediated Down-Regulation of Abscisic Acid Signal Transduction through ABA-Induced Rapid Degradation of RopGEFs

Abstract: The phytohormone abscisic acid (ABA) is critical to plant development and stress responses. Abiotic stress triggers an ABA signal transduction cascade, which is comprised of the core components PYL/RCAR ABA receptors, PP2C-type protein phosphatases, and protein kinases. Small GTPases of the ROP/RAC family act as negative regulators of ABA signal transduction. However, the mechanisms by which ABA controls the behavior of ROP/RACs have remained unclear. Here, we show that an Arabidopsis guanine nucleotide exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 81 publications
0
61
0
Order By: Relevance
“…The small GTPase ROP11 interacts with and protects ABI1 from inhibition by PYL9 (Li et al, 2012). In turn, ABI1 and the other PP2Cs protect the GTP exchange factor RopGEF1 from ABA-induced degradation, thus forming a RopGEF-ROP-PP2C control loop that may counteract leaky ABA signaling by monomeric PYLs in the absence of stress (Li et al, 2016). …”
Section: Aba Signalingmentioning
confidence: 99%
“…The small GTPase ROP11 interacts with and protects ABI1 from inhibition by PYL9 (Li et al, 2012). In turn, ABI1 and the other PP2Cs protect the GTP exchange factor RopGEF1 from ABA-induced degradation, thus forming a RopGEF-ROP-PP2C control loop that may counteract leaky ABA signaling by monomeric PYLs in the absence of stress (Li et al, 2016). …”
Section: Aba Signalingmentioning
confidence: 99%
“…Hypersensitive responses to abscisic acid (ABA)-mediated stomata closure and ABA-inhibited root growth have been reported for ropgef1ropgef4 and ropgef1ropgef4ropgef10 mutant plants (Li and Liu, 2012;Yu et al, 2012). A recent study found that RopGEF1 was targeted for degradation by ABA and functioned in ABA-mediated inhibition of lateral root growth (Li et al, 2016). RopGEF11 has been shown to be involved in root development by interacting with phytochrome (Shin et al, 2010).…”
mentioning
confidence: 99%
“…The deduced amino acid sequence of KAR encodes a highly conserved plant-specific Rop nucleotide exchanger (PRONE) catalytic domain, which is characteristic of the guanine nucleotide exchange factor (GEF) of the Rop GTPase [19], while the N- and C-terminal regions outside of the PRONE domain were highly variable (Figure S3). In angiosperms, Rop signaling mediated by RopGEF is involved in various developmental processes and environmental responses [2025]. KAR is the sole PRONE-type RopGEF gene in the M. polymorpha genome.…”
Section: Resultsmentioning
confidence: 99%